2020
DOI: 10.25259/sni_496_2019
|View full text |Cite
|
Sign up to set email alerts
|

Laser interstitial thermal therapy in neuro-oncology applications

Abstract: Background: Laser interstitial thermal therapy (LITT) is a minimally invasive surgical treatment for multiple intracranial pathologies that are of growing interest to neurosurgeons and their patients and is emerging as an effective alternative to standard of care open surgery in the neurosurgical armamentarium. This option was initially considered for those patients with medical comorbidities and lesion-specific characteristics that confer excessively high risk for resection through a standard craniotomy appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Additionally, LITT may open the blood-brain barrier (BBB) for months, which may pave the way for better penetration of chemotherapeutic agents [6] and macrophage infiltration of the lesion [7]. Studies have demonstrated the efficacy of LITT for multiple indications, including brain metastasis, radiation necrosis, cavernous malformations, epilepsy, gliomas, and meningiomas [2,4,[6][7][8][9][10][11]. In high-grade glioma, complete ablation was associated with longer progression-free survival (PFS) in difficult-to-access regions of the brain [5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, LITT may open the blood-brain barrier (BBB) for months, which may pave the way for better penetration of chemotherapeutic agents [6] and macrophage infiltration of the lesion [7]. Studies have demonstrated the efficacy of LITT for multiple indications, including brain metastasis, radiation necrosis, cavernous malformations, epilepsy, gliomas, and meningiomas [2,4,[6][7][8][9][10][11]. In high-grade glioma, complete ablation was associated with longer progression-free survival (PFS) in difficult-to-access regions of the brain [5].…”
Section: Introductionmentioning
confidence: 99%